The Quadruple Tank Process with an Interaction : A Mathematical Model - Govinda Kumar, E; Shiva ram, B; B.Deepak, U; Sabarinathan, G (International Journal of Engineering and Technology, 2018)
This paper dealt that, the quadruple tanks process with an interaction, which is consisting of four interconnected tanks and included with an interaction of bottom two tanks. The mathematical model of quadruple tankwith interaction is developed throughminimum phase and non-minimum phase by changing a valve position. It described clearly about the mathematical modeling of quadruple-tanks process with an interaction, which is obtained based on minimum and non-minimum characteristics. The obtained process transfer function models are validated using MATLAB simulation. The obtained transfer function models are used to further control and analysis of the same problem.Â Â